Clinical Features Of Iraqi Patients With Tetralogy Of Fallot - Al-Hamash, Sadiq M.; Al-Nasiry, Zuhair; Al-Quraishi, Muthana H. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Tetralogy of Fallot is the most common cyanotic congenital heart disease which represents about 8-10% of all congenital heart diseases. It is characterized by four morphological features, large malalignment ventricular septal defect, Pulmonary stenosis, Overriding of aorta, and Right ventricular hypertrophy. The infant with TOF does well for the first few months of life with minimal or no cyanosis. The cyanosis begins to increase with secondary slow increase in polycythemia as well. Hypercyanotic spells are the most common complicating features of TOF Patients and methods: This is a retrospective study of 200 patients with Tetralogy of Fallot (TOF) referred to Ibn Al-Bitar Center for Cardiac surgery from April 1993 to May 1999. The diagnosis was established by echocardiography, catheterization and angiographic study. For each patient, clinical history, physical examination, O2 saturation and hematocrit level had been reviewed. Results: The patients’ ages ranged from 11 months to 37 years. The weight of 42 patients (22%) and the height of 38 patients (20.5%) were below 3rd centile. There were 60 patients (30%) were polycythemic (hematocrit above 65%). Only 7 patients (14%) had low cyanosis (pink TOF) and one third of the patients had history of hypercyanotic spells. The CNS complications were the most common complications. Conclusions: The study revealed that most of our patients had been delayed in their presentation for proper medical and surgical management. The study showed that most of TOF patients had normal growth pattern and the most important factor affecting the growth was the level of oxygen desaturation and we found high incidence of both infective endocarditis and CNS complications.